Maximal Resection of Tumors Encasing the Internal Carotid Artery and Hindering Internal Carotid Artery Expansion Followed by Revascularization Surgery: A Series of Nine Cases at a Single Tertiary Center - Sun, Yuming; Wang, Long; Shi, Xiangen; Liu, Fangjun (Frontiers in Surgery, 2022)
Purpose: Cerebral reconstruction appears to play a diminished role in managing complex skull base tumors involving vital neurovascular structures. Materials and Methods: Patients with recurrent or progressive middle cranial fossa tumors treated by radical resection followed by extracranial-to-intracranial (EC-IC) bypass from 2014-2019 were included. Balloon test occlusion (BTO) was performed preoperatively. Results: Overall, 9 patients (5 males, 4 females; mean age, 29.9 years) were enrolled. The lesions arose from the parasellar region (3), cavernous sinus (3), petroclival region (2), or orbital apex (1), and all encased the cavernous/petrous portion of the internal carotid artery. Before tumor resection, internal maxillary artery (IMA) bypass was performed for 7 patients, cervical EC-IC bypass was performed for 1 patient, and interposed superficial temporal artery (STA) bypass was performed for 1 patient. BTO failed in 8 patients and was tolerated by one patient. Intraoperative blood flow of the interposed graft was 79.7±37.86 ml/min after IMA bypass, 190.6 ml/min following cervical EC-IC bypass and 75 ml/min after interposed STA bypass. All bypasses were patent on intraoperative indocyanine green angiography. Radical tumor resection was achieved in 5 patients (55.6%), and patency was confirmed postoperatively in 88.8% (8/9) of bypasses. Six patients showed favorable outcomes at discharge. At the 2-year follow-up, 7 patients (77.8%) had favorable outcomes (Karnofsky Performance Scale score>80). At the 1.5-year follow-up, one patient had died due to infarction; at the 3-year follow-up, another patient had developed tumor recurrence despite being asymptomatic. Conclusion: Cerebral bypass remains a vital tool for managing select middle cranial fossa tumors that invade or erode the surrounding neurovasculature or hinder carotid artery expansion and are difficult to resect.